Analisis Implementasi Sistem Coretax pada Siklus Pelaporan Pajak di PT Anugerah Bata Indonesia - Maelani, Puspita; Oktiani, Irma; Ulfa, Muthia; Audinasari, Rifka; Khotimah, Fajriana Khusnul; Widoyoko, Bangun; Sari , Cynthia Dikna; Saputro, Maulana Agung (Annusfy : Journal of Multidisciplinary Research, 2026)
This study aims to analyze the implementation of the CoreTax system in the tax reporting cycle at PT Anugerah Bata Indonesia, identify the challenges faced by the company in the implementation process, and evaluate efforts to address these challenges. The research method used is descriptive qualitative with data collection techniques including in-depth interviews, observation, and documentation. Data were analyzed using a thematic approach to explore the impact of CoreTax implementation on the company's tax reporting. The results show that CoreTax is able to improve reporting efficiency, integrate various tax administration functions, and reduce manual workload